A giant reborn why the US will dominate the 21st century - Overtveldt, Johan van (Chicago B2 Books, 2015)
"An analysis of global economic affairs, making the case that the United States will continue to be the world's sole superpower in the 21st century"--Provided by publisher"
Includes bibliographical references (pages 173 -195) and index.
Keywords: United States -- Economic policy -- 21st century; United States -- Politics and government -- 21st century; United States -- Foreign relations -- 21st century